2016
DOI: 10.1038/srep31150
|View full text |Cite
|
Sign up to set email alerts
|

Schistosome sex matters: a deep view into gonad-specific and pairing-dependent transcriptomes reveals a complex gender interplay

Abstract: As a key event for maintaining life cycles, reproduction is a central part of platyhelminth biology. In case of parasitic platyhelminths, reproductive processes can also contribute to pathology. One representative example is the trematode Schistosoma, which causes schistosomiasis, an infectious disease, whose pathology is associated with egg production. Among the outstanding features of schistosomes is their dioecious lifestyle and the pairing-dependent differentiation of the female gonads which finally leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
170
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(188 citation statements)
references
References 70 publications
(103 reference statements)
18
170
0
Order By: Relevance
“…This conclusion is strongly supported by the transcriptomic data. In addition to down-regulation of eggshell synthesis-associated genes in females, such as putative eggshell protein, trematode eggshell synthesis protein, and tyrosinases after Sj-pp1cs knockdown ( Table 1), stem cell and neoblast-associated genes such as fibroblast growth factor receptor (Sjp_ 0112660), argonaute-2 (Sjp_0045200), and nanos (Sjp_ 0060520) were also down-regulated (genes known to participate in gonadal stem cell activities) (24,54). Among these, fibroblast growth factor receptors are not only involved in regulation and maintenance of proliferating somatic cells but are also required for gonad differentiation and reproduction in S. mansoni (24,55).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is strongly supported by the transcriptomic data. In addition to down-regulation of eggshell synthesis-associated genes in females, such as putative eggshell protein, trematode eggshell synthesis protein, and tyrosinases after Sj-pp1cs knockdown ( Table 1), stem cell and neoblast-associated genes such as fibroblast growth factor receptor (Sjp_ 0112660), argonaute-2 (Sjp_0045200), and nanos (Sjp_ 0060520) were also down-regulated (genes known to participate in gonadal stem cell activities) (24,54). Among these, fibroblast growth factor receptors are not only involved in regulation and maintenance of proliferating somatic cells but are also required for gonad differentiation and reproduction in S. mansoni (24,55).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the host environment, both sexes depend on each other's microenvironment and mating status (i.e., paired versus unpaired) for the maturation of both male and female parasites [37]. A recent study has reinforced this observation of pairing-dependent transcriptome alterations and further demonstrated that about 4000 gonadal expressed genes are regulated by the presence of the opposite gender [38]. The maturation process is reversible when individuals are separated for sufficiently long time.…”
Section: The Environment (E)mentioning
confidence: 99%
“…Expression of Cytoplasmic Polyadenylation Element Binding protein (CPEB) homologs has been detected recently in the germline of the fluke Schistosoma mansoni and the non-parasitic flatworm Macrostomum lignano (Arbore et al, 2015; Cogswell et al, 2012; Lu et al, 2016). Members of the CPEB family of proteins are key regulators of mRNA during metazoan germline development.…”
Section: Introductionmentioning
confidence: 99%